2016
DOI: 10.1071/an14988
|View full text |Cite
|
Sign up to set email alerts
|

Methane production and in vitro digestibility of low quality forages treated with a protease or a cellulase

Abstract: The objective was to assess the impact of application of two enzyme mixtures on the in vitro dry matter digestibility, neutral detergent fibre digestibility, net cumulative gas production and methane production after 24 h of incubation of Milium coloratum (formely Panicum coloratum) and a Patagonian meadow grassland. A protease (Protex 6-L) and a fibrolytic enzyme (Rovabio) were assessed at three application rates (30, 60 and 90 mg/100 mL of distiller water) on the substrates. Meadow samples were higher to Mil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Previous studies showed that higher ivGP was observed in the early incubation intervals with exogenous enzyme treatment of lucerne forage (Colombatto et al, 2007), sugarcane leaves and sorghum straw (Elghandour et al, 2013), and in a grass hay/concentrate substrate (Giraldo et al, 2008). Higher ivGP has been used to validate the effect of fibrolytic enzyme in improving the digestibility of feedstuffs (Cantet et al, 2016). Fibrolytic enzymes act on the slowly but progressively fermentable fraction of feed DM (largely the NDF and ADF) through reduction in cell wall thickness (Van de Vyer & Cruywagen, 2013), allowing rumen microbes and fermentation enzymes an easier access to plant cell constituents (Pinos-Rodríguez et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies showed that higher ivGP was observed in the early incubation intervals with exogenous enzyme treatment of lucerne forage (Colombatto et al, 2007), sugarcane leaves and sorghum straw (Elghandour et al, 2013), and in a grass hay/concentrate substrate (Giraldo et al, 2008). Higher ivGP has been used to validate the effect of fibrolytic enzyme in improving the digestibility of feedstuffs (Cantet et al, 2016). Fibrolytic enzymes act on the slowly but progressively fermentable fraction of feed DM (largely the NDF and ADF) through reduction in cell wall thickness (Van de Vyer & Cruywagen, 2013), allowing rumen microbes and fermentation enzymes an easier access to plant cell constituents (Pinos-Rodríguez et al, 2008).…”
Section: Resultsmentioning
confidence: 99%